Supply Chain Management as a Driver of Competitiveness for Fast Moving Consumer Goods Smes in South Africa - Mathu, Kenneth (European Journal of Applied Sciences, 2021)
Introduction The supply chain management strategy adoption by enterprises in the last four decades, has made enterprises more customer-centric, as they focus on product flow from source to the ultimate end-user. Consequently, the phrase ‘customer is king’ has become synonymous with good customer service. The study explored the coordinated supply chain processes as a competitive advantage for the South African small and medium-sized enterprises (SMEs) in the fast moving consumer goods (FMCGs). Methodology The study was grounded in the theory of competitive advantage and qualitative research methodology and constructivism research paradigm were used. The grocery SMEs from Gauteng province, which is the South Africa’s leading economic hub provided the sample for the study. Non-probability sampling was used in selecting the participants of the study who were the owner/managers of the SMEs. The interview covered enterprise relationship with suppliers of fast moving consumer goods (FMCGs) and third-party logistics (3PL) transportation service. The recorded interviews were transcribed, translated, coded and analysed via content analysis to determine the outcome of the study. Results The results indicated that SCM improved cost-effectiveness through savings on 3PL transportation service optimisation shared amongst the SMEs, improved customer service through supply chain collaboration and recovered value from reverse logistics management.